Nutrition Awareness: Family Practices in Indonesian Borderland - Nahak, Maria Paula Marla; Fouk, Maria Fatimah Wilhelmina Abuk; Naibili, Maria Julieta Esperanca (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Poor family nutritional practice is one of the major leading causes of stunting in children aged 0-59 months. Good family nutrition practices are one of the primary keys to stunting prevention. It can also reduce the prevalence of stunting and the impact it has on families, which are included in the category of stunting risk families. This study aimed to investigate nutrition-aware family practices at Haliwen Health Center, Atambua-one of the border areas of the Republic of Indonesia (RI) and Democratic Republic of Timor Leste (DRTL). It is a descriptive study with a cross-sectional design that took place at the Haliwen Health Center, Belu Regency, East Nusa Tenggara Province, Indonesia, from September 1 to October 30, 2021. A total of 147 families with children aged 0-59 months, were selected by purposive sampling. Most mothers (60%) gave exclusive breastfeeding to infants aged 0-6 months. Most mothers (78%) firstly gave complementary feeding to infants at the age of 6 months, most families and children (94%) ate a variety of nutritional sources, most families (56%) used iodized salt, most infants (95%) aged 6-11 months and children 12-59 months received vitamin A supplements, most (88%) pregnant women received iron supplement at least 90 tablets during pregnancy, most postpartum women (72%) received two capsules of vitamin A supplements. 58.5% of families at the Haliwen Health Center had implemented 75% nutrition-aware family indicators. However, none of them had performed 100% nutrition-aware family indicators. Sustainable assistance needs to be improved to reach 100% nutrition-aware family and implemented in all families.